Activity of Father Władysław Chotkowski (1843–1926) in the Academy of Arts and Sciences and the Polish Academy of Arts and Sciences - Bernadeta Wilk (Folia Historica Cracoviensia)
Władysław Chotkowski (1843–1926), a Catholic priest and patriotic activist, lectured on Church history at the Jagiellonian University in Kraków. The excellent preacher who addressed national and social issues from the pulpit, he delivered eulogies at the funerals of eminent Poles and notable Kraków figures. The article presents the relationship of Władysław Chotkowski with the Academy of Arts and Sciences. In 1883, he was elected a member of the Historical Commission, and in 1901 appointed to the Commission for the History of Polish Literature. Since 1907, he was a corresponding member of the Faculty of History and Philosophy at the Academy of Arts and Sciences. As a researcher of the Church history in Galicia, he participated in the meetings of the faculty, during which he presented the results of his research and scientific work that were published by the Academy of Arts and Sciences as dissertations and monographic works. The text, based on archival materials from the resources of the Archive of Science of the Polish Academy of Sciences (PAN) and the Polish Academy of Arts and Sciences (PAU), fills the knowledge gap in the research on the scientific activity of prelate Władysław Chotkowski in the Academy of Arts and Sciences and the Polish Academy of Arts and Sciences.